Legislative Mobilization in Convergent Directions: Anti-Crisis and Pro-Sustainable Development - Ionel Bostan (CES Working Papers, 2014)
In recent years, the legal steps (regulatory) taken at EU level as well as in each Member State, aimed to determine an ascent of sustainable growth, supported by a substantial degree of structural reforms. Obviously, Romania joined on the line, accounting as a responsibility of the state authorities to implement the European standards of the aforementioned nature, and also to develop and implement various (national) laws in an attempt to achieve faster the macro-stabilization and to strengthen the economic and business environment. In other words, lately, a certain enhancement of the intervention of the executive authority/government by legal means in the economic and business environment occurred, a situation determined, as we will show, by the increasing financial difficulties, to which, as we observe, were associated certain circumstances regarding the environment/sustainable development.
Keywords: K23; 330; laws/regulation; financial crisis; institutional mechanisms; macro-economic; sustainable growth; EU; IMF